(untitled) (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of breathing exercises on anxiety in chronic kidney failure patients undergoing hemodialysis. The method used is a quasi experiment with a two group approach: control group and intervention group pretest-posttest. Data were processed using Wilcoxon and Mann Whitney. The results showed that there was an effect of breathing exercises on anxiety (p value 0.000) and there was a significant difference between the control group and the intervention group (p value 0.000). In conclusion, there is an effect of breathing exercises on anxiety and there is a significant difference between the control group and the intervention group. Keywords: Breathing Exercises, Anxiety, Chronic Kidney Disease